Role of the Gut in Diabetic Dyslipidemia - Stahel, Priska; Xiao, Changting; Nahmias, Avital; Lewis, Gary F. (Frontiers in Endocrinology, 2020)
Type 2 diabetes (T2D) is associated with increased risk of cardiovascular disease (CVD). In insulin resistant states such as the metabolic syndrome, overproduction and impaired clearance of liver-derived very-low-density lipoproteins and gut-derived chylomicrons (CMs) contribute to hypertriglyceridemia and elevated atherogenic remnant lipoproteins. Although ingested fat is the major stimulus of CM secretion, intestinal lipid handling and ultimately CM secretory rate is determined by numerous additional regulatory inputs from nutrients, hormones and neural signals that fine tune CM secretion during fasted and fed states. Insulin resistance and T2D represent perturbed metabolic states in which intestinal sensitivity to key regulatory hormones such as insulin, leptin and glucagon-like peptide-1 (GLP-1) may be altered, contributing to increased CM secretion. In this review, we describe the evidence from human and animal models demonstrating increased CM secretion in insulin resistance and T2D and discuss the molecular mechanisms underlying these effects. Several novel compounds are in various stages of preclinical and clinical investigation to modulate intestinal CM synthesis and secretion. Their efficacy, safety and therapeutic utility are discussed. Similarly, the effects of currently approved lipid modulating therapies such as statins, ezetimibe, fibrates and PCSK9 inhibitors on intestinal CM production are discussed. The intricacies of intestinal CM production are an active area of research that may yield novel therapies to prevent atherosclerotic CVD in insulin resistance and T2D.